Literature Review: Analisis Integrasi Mitigasi Bencana pada Pembelajaran - Titis Wulandari; Yul Ifda Tanjung; Festiyed Festiyed; Asrizal Asrizal; Desnita Desnita; Skunda Diliarosta (Universitas Indraprasta PGRI Jakarta, 2023)
Education has a role in building character and community disaster response through learning in schools. Learning that is integrated with disaster mitigation is one of the efforts to develop the soul (character) in order to have disaster preparedness. This is important to do in order to reduce the impact of the disaster. Research on the integration of disaster mitigation into learning has been carried out but no one has explained explicitly about the integrated disaster mitigation plan into learning. Therefore this study aims to present information related to the technical integration of disaster mitigation in the lessons that have been carried out so that it can enrich the body of knowledge and science and improve disaster preparedness from 7 articles in the EBSCO and Scopus databases with limitations 2017-2022. The literature review method uses the Population, Intervention, Comparison and Outcome (PICO) technique. The procedure for searching and selecting articles in this study used Preferred Reporting Items for Systematic Reviews & Meta-analyses (PRISMA). The results of the research based on the 7 articles that have been reviewed show that the integration of disaster preparedness learning towards disaster preparedness with various levels of education.